Предмет: Физика,
автор: Lenal987654321
C1m1(tсм-t1)=c2m2(t2+tсм) выразить c1 m1 c2 n2 t1 t2
Ответы
Автор ответа:
0
С1=(c2m2(t2-tcм))/(m1(tсм-t1)
m1=(c2m2(t2+tсм))/(C1(tсм-t1))
c2=(C1m1(tсм-t1))/(m2(t2+tсм))
m2=(C1m1(tсм-t1))/(c2(t2+tсм))
t1=(c2m2(t2-tсм)-c1m1tсм)/(-c1m1)
t2=(c1m1(tсм-t1)+c2m2tсм)/c2m2
m1=(c2m2(t2+tсм))/(C1(tсм-t1))
c2=(C1m1(tсм-t1))/(m2(t2+tсм))
m2=(C1m1(tсм-t1))/(c2(t2+tсм))
t1=(c2m2(t2-tсм)-c1m1tсм)/(-c1m1)
t2=(c1m1(tсм-t1)+c2m2tсм)/c2m2
Похожие вопросы
Предмет: Қазақ тiлi,
автор: 170979kuzya
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: Aqua8186
Предмет: Литература,
автор: fasterdo
Предмет: Биология,
автор: ТигранАрифулов